Analysis of plane waves in anisotropic piezothermoelastic diffusive medium. Issue 1 (13th June 2016) - Kumar, Rajneesh; Sharma, Poonam
Abstract : Purpose: – The purpose of this paper is to study the propagation of harmonic plane waves in a homogeneous anisotropic piezothermoelastic diffusive medium. Design/methodology/approach: – After developing the mathematical model and theoretical analysis of the problem, computational work has been performed to study the different characteristics of the plane harmonic waves. Findings: – The existence of waves namely, quasi-longitudinal wave (QP), quasi-thermal wave and quasi-mass diffusion wave have been found which propagates in an anisotropic piezothermoelastic diffusive medium. The different characteristics of waves like phase velocity and attenuation quality factor are computed numerically and presented graphically to show the piezoelectric effect. Originality/value: – A significant piezoelectric effects have been observed on the different characteristics of the waves in an anisotropic piezothermoelastic diffusive medium.